THE THREE PILLARS OF TURKISH POLICY IN AFRICA - Vatanyar S. Yagya; Mariia A. Kolesnikova (Сравнительная политика)
Turkey as a new player in Africa has appeared with the collapse of the bipolar system. Having proclaimed to build a multi-vector policy, Ankara consistently implements the set strategy, which has the character of a comprehensive and long-term program and involves the intensification of cooperation with African countries in the political, economic and humanitarian spheres. Turkey systematically promotes its political line in the region and has the support of influential African elites in many countries of the continent. At the same time the ruling Justice and Development Party, helping to strengthen the economic positions of Turkish businessmen abroad, successfully copes with resolving  problems of domestic policy by increasing the export of Turkish goods, spreading the idea of "moderate Islam" on the whole continent. Projects in the humanitarian field that are implemented by the Turkish government and non-governmental organizations are also successful. However, there are  series of tactical complexities associated with the aggravation of the previous and the emergence of new problems caused by various factors of political, economic and ideological origins. Nevertheless, Ankara is suggested to continue its attempts to conduct an active policy aimed at the conquest of regional leadership and strengthening its presence in Africa in the future.